130k views
5 votes
Which expression shows

Which expression shows-example-1

2 Answers

5 votes
A)

You do what’s in the ( )


(5+6)= 11 so 11+7
And (6+7) = 13 so it’s 5+13
User Atri
by
4.6k points
1 vote

Answer:

Option A - ( 5 + 6 ) + 7 = 5 + ( 6 + 7 )

Explanation:

In this question we are asked about which expression shows that

11 + 7 = 5 + 13

For this, the answer will be

Option a that is ( 5 + 6 ) + 7 = 5 + ( 6 + 7 )

Because ( 5 + 6 ) = 11

Then +7 at the other side 5 add with ( 6 + 7 ) that is equal to 13,

This is the method we do step by step,

First ( 5 + 6 ) is 11

Then another side ( 6 + 7 ) = 13

Then we add 11 with 7 and another side 5 with 13,

Therefore, option a ( 5 + 6 ) + 7 = 5 + ( 6 + 7 ) is the right answer

User Web  Hopeful
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.